POTENSI PSEUDOMONAD FLUORESEN ISOLAT CAS3 PADA BEBERAPA FORMULA DENGAN PENAMBAHAN STABILIZER GLISEROL DALAM MENGENDALIKAN BLOOD DISEASE BACTERIA (BDB) SECARA INVITRO - Advinda, Linda; Fifendy, Mades; Rahmadeni, Yossi (Sainstek : Jurnal Sains dan Teknologi, 2014)
The purpose of this study was to determine the potential of fluorescent pseudomonads on some carrier with the addition of stabilizer glycerol in controlling Blood Disease Bacteria invitro. The experiment was conducted from May to July 2013, housed in the Laboratory of Plant Physiology, FMIPA UNP. Parameters measured were the amount of inhibition zone diameter fluorescent pseudomonads in controlling BDB CAS3 invitro. Observations preservation is done every 10 days until a preservation period of 60 days. This study is an experiment in completely randomized design (CRD) with 9 treatments and 3 replications. The treatments were fluorescent pseudomonads carrier CAS3 on tapioca (glycerol addition of 0,03 mL, 0,04 mL and 0,05 mL); carrier CAS3 fluorescent pseudomonads in rice flour (glycerol addition of 0,03 mL, 0,04 mL and 0,05 mL); carrier CAS3 fluorescent pseudomonads on talc (glycerol addition of 0,03 mL, 0,04 mL and 0,05 mL). Inhibition zone diameter data were analyzed using ANOVA at 5% significance level and continued with DNMRT test at 5% significance level. The results showed that the large inhibitory zone formed around the Blood Disease Bacteria vary. Results of analysis of variance on the preservation period of 10 days was significantly different at DNMRT further test, with the largest inhibition zone that is in treatment F (6,41mm) and the lowest in treatment I (1.15mm), whereas the preservation period of 20 to 60 days is not significantly different. All types of fluorescent pseudomonads carrier Cas3 potential in controlling Blood Disease Bacteria invitro.Key words : pseudomonad fluoresen, Blood Disease Bacteria, Glycerol